(untitled) (Research, Society and Development, 2021)
From the articles found, the authors made a proposal for guidelines for the use of exams based on scientific evidence, for the most used imaging exams in dentistry. The selection of articles was based on the following inclusion criteria: papers published between January/2000 and December/2020, literature reviews (systematic, integrative or descriptive), main theme related to the indication of dental radiographs and protocols for the indication of exams imaging devices used in dentistry. Collaborating with the public and supplementary health ecosystem and analyzing the rational use of resources, this work also aims to help entities and professionals in the area to carry out a prior analysis based on scientific consensus that considers the patient’s age group and clinical situation for ordering dental imaging exams. Before requesting any complementary exam, a careful clinical evaluation is recommended. This process allows the adoption of the best dental practices and evidence-based clinical decision-making that includes not only the best treatment proposal, but also the best treatment opportunity and imaging exam selection. The proposed Guidelines for Image Examinations in Dentistry can be used by all actors involved in the provision of dental services and, due to the advancement of technology and aiming at maintaining in accordance with current standards, data update every two years.